Trends & Determinants of Capital Structure of U.K. Firms - Vora, Rajan (2009)
This paper investigates the determinants of capital structure in firms from the United Kingdom. It aims to determine which of the theories of capital structure is most relevant and applicable to these firms. It intends to compare the results to previous empirical and theoretical predictions. The study includes 81 companies from 10 different industries from 8 different years from 2001-2008. A panel data regression and an ANOVA test is run to analyze what are the determinants of a firm’s short term and long term leverage and how do these determinants influence the capital structure decisions. The impact of industry classification is also captured by the ANOVA test. The industries are introduced as dummy variables in the analysis. Each of the tests are run on Long-Term Leverage as well as Short-Term Leverage as dependent variables. Firm Size, Profitability, Asset Tangibility, Growth Opportunities, Non-Debt Tax Shields and Volatility are the independent variables included. Most of the factors follow the predictions of the Pecking Order Theory of Capital Structure. This states that firms follow a certain order in order to raise finance. However no conclusive evidence is found supporting one single theory that can explain the capital structure decisions of a firm in the United Kingdom. The determinants still remain a puzzle which would be debatable for years to come.